REGULATORY CONVERGENCE OR DIVERGENCE? A COMPARATIVE ANALYSIS OF SHARIA ECONOMIC DISPUTE RESOLUTION IN INDONESIA, MALAYSIA, AND THE GCC - Muhammad Wahid Cahyana; Rika Novitasari; Tikka Dessy Harsanti; Meera Gupta (Yayasan Adra Karima Hubbi, 2026)
Sharia economic dispute resolution is a critical component of Islamic finance, with varying institutional frameworks and procedural approaches across Southeast Asia and the Gulf Cooperation Council (GCC) states. Differences in tribunal specialization, arbitration adoption, and procedural codification create both convergence and divergence in dispute management practices. This study aims to provide a comparative analysis of Sharia economic dispute resolution mechanisms in Indonesia, Malaysia, and selected GCC countries, identifying patterns of regulatory alignment, institutional effectiveness, and procedural standardization. A qualitative-dominant research design was employed, combining doctrinal legal analysis, evaluation of tribunal guidelines, review of case law, and semi-structured expert interviews. Data were synthesized to assess tribunal specialization, resolution duration, arbitration use, and procedural compliance across jurisdictions. Results indicate that Malaysia and GCC states exhibit higher tribunal specialization, faster case resolution, greater adoption of arbitration frameworks, and more standardized procedures compared to Indonesia. Indonesia demonstrates longer case durations, lower procedural codification, and limited tribunal specialization, highlighting areas of regulatory divergence. The study concludes that regulatory convergence is partially evident between Malaysia and GCC, while Indonesia represents a divergent model, emphasizing the role of institutional design, procedural codification, and arbitration mechanisms in effective Sharia dispute resolution. Findings offer implications for harmonization initiatives, capacity building, and cross-border policy coordination in Islamic finance.